An experimental and numerical study of the solid particle erosion damage in an industrial cement large-sized fan. (April 2023) - Fortini, Annalisa; Suman, Alessio; Zanini, Nicola
Highlights: Failure analysis of an erosion-damaged large-sized centrifugal fan employed in a clinker plant. Development of a combined approach (tailored experimental wear tests and numerical analyses) to study the solid particle erosion phenomenon. Effective prediction capability of design solutions and service intervals resulting in economic benefits for manufacturers and operators. Abstract: The present paper addresses the wear failure analysis of a large-sized centrifugal fan operating in a cement clinker grinding plant. Within cement production, the calcination at middle and high-temperature values (from 120 °C to 400 °C depending on the process parameters) of the raw material requires such a process fan, which also ensures the draft and feed of the flue gases and combustion air needed for the operation of the main equipment of the cement factory. To detect and analyze the impact conditions within the heavy-duty fan, Computational Fluid Dynamics (CFD) analyses were performed. The analysis of the numerical results shows that the relevant fan surfaces are affected by different impact velocities and angles, generating non-uniform erosion patterns similar to the on-field detections. Besides, the obtained comprehensive description of the flow and contaminants behaviors through the entire flow path enables setting up the subsequent experimental investigation. The erosive wear behavior of a Fe-Cr-C hardfacing cast iron and wear-resistant steel was tested through a test rig constructed for the purpose of being in accordance with the ASTM G76 standard. The test bench was adapted to manage the raw meal powder used in the cement factory to reproduce the actual operating conditions. The results show a greater capability of Fe-Cr-C hardfacing cast iron to face the erosion phenomenon in terms of lower values of material loss over the exposure time. These findings, coupled with the metallographic analysis to detect the erosion mechanisms (ductile and/or brittle), help a better prediction of the fan operating life. The investigation showed the reliability of the numerical/experimental coupled approach in assessing the actual erosion magnitude and the influence of the impact angle on the erosion phenomena. This coupled approach gains a further understanding of the proper design of manufacturing and maintenance activities, covering several project steps from material selections to the scheduled and overhaul operations. A reliable operating-life prediction allows manufacturers and operators to obtain production and economic goals.